2021
DOI: 10.1080/21655979.2021.1967077
|View full text |Cite
|
Sign up to set email alerts
|

Exosomal circular RNA circ_0074673 regulates the proliferation, migration, and angiogenesis of human umbilical vein endothelial cells via the microRNA-1200/MEOX2 axis

Abstract: Circular RNAs (circRNAs) are implicated in the pathogenesis of gestational diabetes mellitus (GDM). The aim of this study was to investigate the roles and molecular mechanism underlying the effects of circ_0074673 in GDM. Exosomal morphology was visualized by transmission electron microscopy (TEM), while exosomal size and concentration were determined by nanoparticle tracking analysis (NTA). The expression of CD9 and CD63 was measured by western blotting. The levels of circ_0074673, miR-1200 and mesenchyme hom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…HUMSC-EXOs regulates the membrane translocation of glucose transporter-4 (GLUT4) and the activation of enzymes implicated in glucose metabolism to improve glucose uptake and glycogen deposit. In addition, an in vitro study on the roles of human umbilical vein endothelial cells-derived exosomal circNRA demonstrated that the expression of circ_0074673 was upregulated in exosomes isolated from GDM patients and in human umbilical vein endothelial cells incubated with exosomes [ 36 ]. Notably, the knockdown of circ_0074673 alleviates the suppression of proliferation, migration, and angiogenesis of umbilical vein endothelial cells by directly sponging miR-1200 to target MEOX2.…”
Section: Discussionmentioning
confidence: 99%
“…HUMSC-EXOs regulates the membrane translocation of glucose transporter-4 (GLUT4) and the activation of enzymes implicated in glucose metabolism to improve glucose uptake and glycogen deposit. In addition, an in vitro study on the roles of human umbilical vein endothelial cells-derived exosomal circNRA demonstrated that the expression of circ_0074673 was upregulated in exosomes isolated from GDM patients and in human umbilical vein endothelial cells incubated with exosomes [ 36 ]. Notably, the knockdown of circ_0074673 alleviates the suppression of proliferation, migration, and angiogenesis of umbilical vein endothelial cells by directly sponging miR-1200 to target MEOX2.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, exosomal circ_0074673 is increased in the exosomes from GDM patients and in human umbilical vein endothelial cells (HUVECs) cocultured with the exosomes. Silencing circ_0074673 promotes the proliferation, migration, and angiogenesis of HG-HUVECs via the miR-1200−MEOX2 axis ( 62 ). In summary, a drug that maintains normal function of the cells by regulating circRNA expression levels may open new avenues for GDM therapy.…”
Section: Role Of Circrnas In Gdmmentioning
confidence: 99%
“…Currently, the understanding of the role of exosomal circRNA in the molecular mechanisms and possible clinical applications in leukemia are very limited and need further study. It has been extensively verified in solid tumors that exosomal circRNAs participate in numerous cancer biological processes including tumorigenesis, proliferation, angiogenesis, metastasis, drug resistance, etc ( Liu et al, 2020 ; Xie et al, 2020 ; Xu J. et al, 2020 ; Huang et al, 2021 ). Xie et al (2020) reported that exosomal circSHKBP1 regulated the miR-582-3p/HUR/VEGF pathway, suppressed HSP90 degradation, and promoted GC progression.…”
Section: Role Of Exosomal Circrnas In Leukemiamentioning
confidence: 99%